2002
DOI: 10.1093/jexbot/53.372.1227
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction during oxidative stress

Abstract: As an unfortunate consequence of aerobic life, active oxygen species (AOS) are formed by partial reduction of molecular oxygen. Plants possess a complex battery of enzymatic and non-enzymatic antioxidants that can protect cells from oxidative damage by scavenging AOS. It is becoming evident that AOS, which are generated during pathogen attack and abiotic stress situations, are recognized by plants as a signal for triggering defence responses. An overview of the literature is presented on the signalling role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
251
0
19

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 597 publications
(276 citation statements)
references
References 100 publications
6
251
0
19
Order By: Relevance
“…However, regarding the complex composition of sunflower leaves extract (Macias et al, 2002) it is not possible to conclude that there is a specific effect of phytotoxic compounds on antioxidant enzymes. Furthermore, it is known that activity and expression of most antioxidant enzymes is stimulated by ROS accumulation (Vranova et al, 2002;de Gara et al, 2003;Apel and Hirt, 2004). The first effect of sunflower phytotoxicity is a dramatic increase in H 2 O 2 concentration and an inhibition of GR activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, regarding the complex composition of sunflower leaves extract (Macias et al, 2002) it is not possible to conclude that there is a specific effect of phytotoxic compounds on antioxidant enzymes. Furthermore, it is known that activity and expression of most antioxidant enzymes is stimulated by ROS accumulation (Vranova et al, 2002;de Gara et al, 2003;Apel and Hirt, 2004). The first effect of sunflower phytotoxicity is a dramatic increase in H 2 O 2 concentration and an inhibition of GR activity.…”
Section: Discussionmentioning
confidence: 99%
“…10g and h) (Huner et al 1998;Tikkanen and Aro 2012). Hydrogen peroxide is the most stable and longdistance ROS signaling molecule that regulates stress responses and developmental processes in plants (Vranová et al 2002). Vandenabeele et al (2002) showed that hydrogen peroxide could provoke transcriptional responses that mimicked both biotic and abiotic stresses.…”
Section: (D)mentioning
confidence: 99%
“…Water deficits in soil environment also influence solute transport (ion and nutrient uptake of plants) to larger extent, which effects on photosynthetic reactions in plant chloroplasts in many ways [117,120,131,135,[139][140][141][142][143][144][145][146][147]. This is the reason that ion homeostasis and redox state have been brought to attention [4][5][6][7][21][22][23][24][25][26][27][28][29][111][112][113][114][115][116][117][118][119]. The series of the above reactions and processes occurring at different soil-root biointerfaces is regulated and controlled by plant gene regulatory network system spatially and temporally on the basis of responding to plant developmental cues, through which plants can elegantly respond to the changing environment [8][9][10][11][12][13][14][15][16][17]…”
Section: Physiological Theories: Understanding Higher Plant Physiologmentioning
confidence: 99%
“…However, in addition to biotic stress factors, disturbances of extreme or even mild abiotic stress are supposed to account for a high amount of unachieved potential in plant production all over the globe [22,23,72,73,77,78]. Diverse forms of abiotic stresses may occur, including drought, cold and freezing, heat, salinity, nutrient deficiency, toxic heavy metals, oxidative stress as well as oxygen shortage, and mechanical stress [37,88,115]. Although it is accepted that diverse environmental stress factors never act alone, experimental study of plant responses to abiotic stresses is normally restricted to plant reactions on isolated stress factors [2][3][4][5][6]134,[144][145][146][147].…”
Section: Introductionmentioning
confidence: 99%